2002
DOI: 10.1046/j.1365-2141.2002.03517.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy‐related chronic myelogenous leukaemia following autologous stem cell transplantation for Ewing's sarcoma

Abstract: Summary.A 17-year-old Japanese woman with Ewing's sarcoma was initially treated with conventional chemotherapy and local irradiation, and then with high-dose chemotherapy supported by autologous peripheral blood stem cell transplantation. Four years later she was diagnosed with chronic myelogenous leukaemia (CML). The BCR/ABL fusion gene was detected in both peripheral blood and bone marrow cells by reverse transcription-polymerase chain reaction, but not in the harvest product of peripheral blood stem cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The only documented case of CML occurring as a secondary potentially therapy-related cancer is that of a 17-year-old patient who developed CML 4 years after chemotherapy for Ewing sarcoma [8].…”
Section: Discussionmentioning
confidence: 99%
“…The only documented case of CML occurring as a secondary potentially therapy-related cancer is that of a 17-year-old patient who developed CML 4 years after chemotherapy for Ewing sarcoma [8].…”
Section: Discussionmentioning
confidence: 99%
“…One patient was reported with lymphoid blast crisis of CML that was p210 + at 7 years after chemoradiotherapy for NHL [24]. One 17-year-old patient was reported with p210 + t-CML after completing chemoradiotherapy for ES, followed by an autologous PB HCT [25]. Moss et al reported one case of t-CML in a patient treated for a Wilms tumor [26].…”
Section: Discussionmentioning
confidence: 99%
“…Only rarely have cases been reported in which treatment-related CML developed after high-dose chemotherapy, radiation and autologous peripheral blood stem cell transplantation (16). Vincristine, adriamycin, cyclophosphamide, actinomycin-D, carboplastin, etoposide, ifosfamide and local irradiation for the treatment of Ewing's sarcoma developed secondary CML (16). However, these secondary CML patients were often negative for the BCR/ ABL gene, and there are no reports of the use of only immunosuppressive drugs, including cyclosporine and cyclophosphamide, causing secondary CML.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the BCR/ ABR fusion gene characteristic of CML developed after 10 months of treatment with cyclosporine and before any morphological abnormality appeared, suggesting that hematopoietic system malignancy might develop soon after cyclosporine treatment. Only rarely have cases been reported in which treatment-related CML developed after high-dose chemotherapy, radiation and autologous peripheral blood stem cell transplantation (16). Vincristine, adriamycin, cyclophosphamide, actinomycin-D, carboplastin, etoposide, ifosfamide and local irradiation for the treatment of Ewing's sarcoma developed secondary CML (16).…”
Section: Discussionmentioning
confidence: 99%